Dietary patterns of persons with chronic conditions within a multi-ethnic population: results from the nationwide Knowledge, Attitudes and Practices survey on diabetes in Singapore - Yeow Wee Brian Tan; Jue Hua Lau; PV AshaRani; Kumarasan Roystonn; Fiona Devi; Ying Ying Lee; Clare Whitton; Peizhi Wang; Saleha Shafie; Sherilyn Chang; Anitha Jeyagurunathan; Boon Yiang Chua; et al. (BMC, 2022)
Abstract Background Chronic conditions are a leading cause of death and disability worldwide and respective data on dietary patterns remain scant. The present study aimed to investigate dietary patterns and identify sociodemographic factors associated with Dietary Approaches to Stop Hypertension (DASH) scores within a multi-ethnic population with various chronic conditions. Methods The present study utilised data from the 2019-2020 Knowledge, Attitudes, and Practices study on diabetes in Singapore - a nationwide survey conducted to track the knowledge, attitudes, and practices pertaining to diabetes. The study analysed data collected from a sample of 2,895 Singapore residents, with information from the sociodemographic section, DASH diet screener, and the modified version of the World Mental Health Composite International Diagnostic Interview (CIDI) version 3.0 checklist of chronic physical conditions. Results Respondents with no chronic condition had a mean DASH score of 18.5 (±4.6), those with one chronic condition had a mean DASH score of 19.2 (±4.8), and those with two or more chronic conditions had a mean DASH score of 19.8 (±5.2). Overall, the older age groups [35- 49 years (B = 1.78, 95% CI: 1.23 - 2.33, p <0.001), 50-64 years (B = 2.86, 95% CI: 22.24 - 3.47, p <0.001) and 65 years and above (B = 3.45, 95% CI: 2.73 - 4.17, p <0.001)], Indians (B = 2.54, 95% CI: 2.09 - 2.98, p <0.001) reported better diet quality, while males (B = -1.50, 95% CI: -1.87 - -1.14, p <0.001) reported poorer diet quality versus females. Conclusion Overall, respondents with two or more chronic conditions reported better quality of diet while the sociodemographic factors of age, gender and ethnicity demonstrated a consistent pattern in correlating with diet quality, consistent with the extant literature. Results provide further insights for policymakers to refine ongoing efforts in relation to healthy dietary practices for Singapore.